2014
DOI: 10.22260/isarc2014/0070
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Energy Usage Using Historical Data and Linear Models

Abstract: Abstract:This paper presents a method to predict energy usage, based on weather conditions and occupancy, using a multiple linear regression model (MLR) in research office buildings. In this study, linear regression models of four research office sites in different regions of New Zealand were selected to show the capability of simple models to reduce margins of error in energy auditing projects. The final linear regression models developed were based on monthly outside temperatures and numbers of full time emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…It is easy to develop and implement [38] and is widely used in the prediction of energy use. For example, Safa et al [39] presented a method to predict energy use in office buildings for the purpose of energy auditing. The study showed the capacity of simple models where the final regression model was based on outdoor temperature and occupancy with a monthly resolution.…”
Section: Energy Prediction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is easy to develop and implement [38] and is widely used in the prediction of energy use. For example, Safa et al [39] presented a method to predict energy use in office buildings for the purpose of energy auditing. The study showed the capacity of simple models where the final regression model was based on outdoor temperature and occupancy with a monthly resolution.…”
Section: Energy Prediction Methodsmentioning
confidence: 99%
“…Catalina et al [40] developed a regression model for predicting the monthly space heating demand for residential buildings while another approach developed a generic equation of three variables for predicting the heating demand in apartments blocks [41]. The MLR method has also been applied with success in energy forecasting for swimming pool buildings [38,39].…”
Section: Energy Prediction Methodsmentioning
confidence: 99%
“…Specifically, two different statistical models are used in this study. These models are multiple linear regression model [12][13][14] and Box-Jenkins' autoregressive model of order 1 [15][16][17][18][19]. It also provides the source and method of data collection.…”
Section: Methodsmentioning
confidence: 99%
“…This model's coefficient of determination (R 2 ), the indication of the goodness of fit, was 0.7263, with all variables significantly contributing to the model. However, when the residual plot for this model was examined it showed a clear pattern that suggested the possibility of the need for variable transformation [19].…”
Section: Forecasting With Linear Modelingmentioning
confidence: 99%
“…This final linear model was chosen to be more successful over other non-linear methods as it had the highest R 2 value (0.7711), which indicates high correlation between predicted and the actual observed values. The other comparison metric that was used to evaluate this model against others was root mean squared error (RMSE) (2219.7), which measures the standard deviation of the model's prediction error, and thus a lower value is more desirable [19]. One of the results of creating a linear model is that the coefficients of the model indicate the relationship of each feature to the response variable.…”
Section: Forecasting With Linear Modelingmentioning
confidence: 99%